100 Years of Medical Countermeasures and Pandemic Influenza Preparedness - Jester, Barbara J. (Am J Public Health, 2018)
The 1918 influenza pandemic spread rapidly around the globe, leading to high mortality and social disruption. The countermeasures available to mitigate the pandemic were limited and relied on nonpharmaceutical interventions. Over the past 100 years, improvements in medical care, influenza vaccines, antiviral medications, community mitigation efforts, diagnosis, and communications have improved pandemic response. A number of gaps remain, including vaccines that are more rapidly manufactured, antiviral drugs that are more effective and available, and better respiratory protective devices.